MOLECULAR DETECTION OF Coxiella burnetii THE CAUSE OF ZOONOSIS Q FEVER IN VARIOUS ORGANS OF CATTLE IN BANDUNG REGENCY - Purnamiharja, Tsulatsy Puspitasari; Juniantito, Vetnizah; WoroWiranti, Rahayu; Setiyono, Agus (Jurnal Kedokteran Hewan, 2023)
Primary objective of this study was to ascertain the presence of Coxiella burnetii (C. burnetii) as the causative of Q fever in cattle within Bandung Regency. Tissue samples were procured from 240 slaughtered cattles in abattoirs across Bandung Regency. Each breed of cattle consists of Brahman cross (BX), Simmental, Limousin, Friesien Holstein crossbreed, and Friesien Holstein (FH) with total of 192, 3, 13, 29, and 3, respectively. Detection method employed was nested-Polymerase Chain Reaction (PCR) to identify the presence of C. burnetii Deoxyribonucleic Acid (DNA) within tissue samples. Positive samples underwent further examination employing hematoxylin-eosin (HE) staining to identify lesions attributed to C. burnetii. Five BX cattle were identified as positive for C. burnetii in lungs and heart. However, histopathological analysis of both organs did not reveal any notable changes. These findings suggest the occurrence of C. burnetii infection in cattle within Bandung Regency, without specific histopathological changes indicative of Q fever lesions. In conclusion, presence of asymptomatic C. burnetii infections should be regarded as a significant threat to human health.